Physicians’ knowledge, practice, and attitudes on fertility and pregnancy-related issues in young women with advanced breast cancer: results of the ABC6 and ABC7 survey - Simone Nardin; Luca Arecco; Virginia Delucchi; Eva Blondeaux; Mihaela Stana; Luciana de Moura Leite; Luiza Nardin Weis; Giang Pham Hoang; Arianna Daneri; Francesca Bruzzone; Arianna Meacci; Chiara Molinelli; et al. (Breast)
Background: Fertility and pregnancy-related issues are critical for young patients with breast cancer. No proper evidence exists on physicians' knowledge, practice, and attitudes on dealing with these concerns in the specific group of patients with advanced disease. Methods: A 26-item questionnaire was administered via e-mail in December 2023 to physicians who attended the ABC6 consensus conference (virtually, November 2021) and those who were registered for the ABC7 consensus conference (Lisbon, November 2023). The questionnaire was divided into 3 main sections: 1) demographic, medical training, and background information; 2) knowledge, practice, and attitudes of physicians towards fertility preservation and pregnancy-related issues in patients with advanced breast cancer; 3) approach to hypothetical clinical cases. Results: A total of 133 physicians completed the survey. Most reported discussing always (40.6 %) or usually (36.1 %) the possible treatment-related loss of ovarian function in patients with advanced breast cancer. Regarding fertility preservation and pregnancy-related issues, 23.3 % would always feel comfortable discussing these topics with patients, and 45.9 % would feel comfortable depending on the clinical situation. 20.3 % reported not prescribing any type of contraception, and 10–20 % would prescribe treatments that are contraindicated during pregnancy. Conclusions: Our survey showed that many concerns exist when discussing and dealing with fertility and pregnancy-related issues in patients with advanced breast cancer. It is essential to increase physicians' awareness on how to address fertility and pregnancy-related issues in patients with advanced breast cancer, especially as oncological treatments continue to improve, resulting in longer survival and, in some cases, potential cure.